Comparison of pre-and postoperative medication costs in patients who underwent bariatric surgery - a nationwide data analysis - Magdalena Osińska; Yaroslav Sanchak; Andrzej Śliwczyński; Edward Franek; Edward Franek; Magdalena Walicka; Magdalena Walicka (Frontiers Media S.A., 2024)
IntroductionBariatric surgery has known health benefits and may lower the medication-related costs. This study aimed to assess the cost of medications prior to and after bariatric surgery in the Polish nationwide registry.MethodsThe study included 2,390 adults. The analysis was conducted separately for a 12-month pre-operative period, and a 12-month postoperative period. The total costs of medication and cost per anatomical therapeutic chemical group were assessed and the mean cost per patient in the preoperative and postoperative periods was compared.ResultsThe study showed a significant increase in the overall medication costs and mean costs of medications per patient in the year after bariatric surgery. This increase was related mainly to low-molecular-weight heparins used in the 1st month after surgery. Alternatively, costs of medication used in the cardiovascular system diseases and anti-infectives decreased significantly. The total costs of hypoglycemic agents were reduced by 46%, antihypertensive medications by 29%, and lipid-lowering drugs by 38.ConclusionsIn general, medication costs are higher in the first year after surgery. The increase results from the perioperative use of low-molecular-weight heparins, whereas a significant cost reduction of glucose-, lipid-lowering, antihypertensive, and anti-infective medications was observed.